Transformasi Ekonomi Desa melalui Pemberdayaan UMKM Kripik Pisang dan Gadung di Dusun Wates dalam Mendorong Kewirausahaan dan Pengembangkan Industri Kreatif sebagai Implementasi Asta Cita 3 - Novandi Dwi Putra; Rangga Fajar Ardiansyah; Muhammad Rama Sabillah Fitri Andani; Dhimas Yoga Pratama; Muhammad Rizky Idris; Aden Alvies Adika Satia Anur Rajaya; Miftaqul Fanesya; Oktavia Ramadhanti; Bintang Aditya Nurhakim; Denis Bayu Saputri; Puput Dyah Purwanti; Erykhah Dwi Cahyani; Anita Rah Ayu Utaminingtyas; Vindi Ratna Sary; Amanda Shafa Anindya Putri; Halisa Fauziah; Rizki Nur Prasetya; Maulana Fathur Roziq; Regyna Twinanda Aswin Putri; Muhammad Hafidz Prayoga; Yuda Yuda; Fina Andita; Ayu Wulandari; Atik Damayanti; Christian Daniel Roger Lamia; Lanang Abdillah Azka Rokhim Anas; Elva Nabilah Rifah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
The community service activity conducted in Dusun Wates, focusing on the empowerment of Ibu Siti’s UMKM (Small and Medium Enterprises) producing Banana and Gadung Chips, has shown significant results in improving entrepreneurial capacity and social transformation within Ibu Siti’s family. This research aims to explore the outcomes of the community service program, linking the findings to theories of entrepreneurship, community empowerment, and social change. The activities involved managerial assistance, product rebranding, and online marketing, which led to better management practices, an improved product identity, and increased market reach. The application of digital marketing proved effective in expanding market access for local products, contributing to the economic growth of the family. This study also highlights the importance of family-based entrepreneurship in achieving sustainable social and economic change. The results are aligned with the findings of previous studies, such as those by Wahyuni (2022) and Raharjo (2021), and suggest that the integration of technology and local leadership can significantly drive social transformation at the community level.